DFT study of Interstellar PANH: Vibrational spectra of anionic and cationic variants. Issue 7 (1st October 2022) - Devi, Gauri; Pathak, Amit; Vats, Akant
Abstract: Polycyclic aromatic Hydrocarbons are present in the universe in varied forms and are extensively studied over the years to account for the complex natured Aromatic Infrared Bands (AIBs). As an abundant element in the interstellar medium, nitrogen may substitute carbon atoms in the aromatic rings of PAHs to form Polycyclic Aromatic Nitrogen Heterocyclic (PANH) molecules. These PANH molecules can have new emission features and may contribute to some of the AIBs. Extreme conditions of the ISM may support PAH and/or PANH molecules in the formation of their cationic or anionic forms to further explain the AIBs. The present work reports DFT study of PANH molecules and their ionized variants and discusses their IR spectroscopic features in the 6–10 μm region.